Pelaksanaan Perencanaan Pulang Pasien Berbasis Theory Of Caring Swanson pada Pasien Stroke - Khairunisa, Fatimatuzzahra; Triharini, Mira; Has, Eka Mishbahatul Mar’ah (Journal of Telenursing (JOTING), 2024)
This study aims to identify the effectiveness of nurses in carrying out discharge planning for stroke patients and their families based on the components of Swanson's Theory of Caring. The research method used is a systematic review through databases and electronic websites, namely Scopus, Sciencedirect, ProQuest, Research Gate, PubMed and Google Scholar. The research results showed that of the 15 research articles there were articles that reported an increase in knowledge of stroke patients and their families after being given discharge planning so that they could improve care after being at home. Conclusion: Discharge planning based on Swanson's Caring Theory involves five components, namely maintaining belief, knowing, being with, doing for, enabling. There is effectiveness of nurses in implementing caring-based discharge planning for patients with stroke. Keywords: Caring, Patient Discharge Planning, Stroke